Swing options in commodity markets: a multidimensional Lévy diffusion model - Eriksson, Marcus; Lempa, Jukka; Nilssen, Trygve Kastberg (Mathematical methods of operations research (Heidelberg, Germany), 2014)
We study valuation of swing options on commodity markets when the commodity prices are driven by multiple factors. The factors are modeled as diffusion processes driven by a multidimensional Lévy process. We set up a valuation model in terms of a dynamic programming problem where the option can be exercised continuously in time. Here, the number of swing rights is given by a total volume constraint. We analyze some general properties of the model and study the solution by analyzing the associated HJB-equation. Furthermore, we discuss the issues caused by the multi-dimensionality of the commodity price model. The results are illustrated numerically with three explicit examples.